Comportamiento agronómico de cinco hortalizas de hojas con tres abonos orgánicos en la finca “La Vaca que Ríe”, cantón El Empalme, provincia del Guayas. - Amancha Martínez, Gorky Emilio (2013)
The present investigation had as objective to determine the agronomic behavior of five vegetables with three organic payments in the property "The Cow that Laughs", canton The Connection, county of the Guayas. This investigation was carried out in the property "The Cow that Laughs", enclosure Santa Lucía, parish The Rosario, canton the Connection, county of the Guayas. Is their geographical location of 1˚2’ 35.3” south latitude and 79˚46’42.1” of longitude west, with an altitude of 54 msnm, did the investigation have a duration of 180 days. A Design of Complete Blocks was used at random (DBCA) for each vegetable with three organic payments a witness and three repetitions. To determine the difference among the stockings of the treatments the test of multiple ranges it was used from Tukey to 5% of probability. The Coefficient of Variation is expressed in percentage. Of the results we can say that excellent yields were obtained with the use of organic payments, highlighting the T2 (Hyacinth of water) with the one that was obtained better productions. The great yield should be pointed out obtained with the witness due to the quality of the floor. The best relationship B/C was obtained with the witness, being the reason of this the fertility of a floor managed organically with respect and under a philosophy of healthy coexistence with the elements.